Evaluation of Gut Microbiota in Healthy Persons and Type 1 Diabetes Mellitus Patients in North-Western Russia - Alexei B. Chukhlovin; Vasilisa V. Dudurich; Aleksey V. Kusakin; Dmitry E. Polev; Ekaterina D. Ermachenko; Mikhail V. Aseev; Yuri A. Zakharov; Yuri A. Eismont; Lavrentii G. Danilov; Oleg S. Glotov (Microorganisms, 2023)
Bacterial microbiota in stool may vary over a wide range, depending on age, nutrition, etc. The purpose of our work was to discriminate phyla and genera of intestinal bacteria and their biodiversity within a healthy population (North-Western Russia) compared to the patients with type 1 diabetes mellitus (T1DM). The study group included 183 healthy persons 2 to 53 years old (a mean of 26.5±1.0 years old), and 41 T1DM patients (mean age 18.2±1.8 years old). The disease onset was at 11±1.5 years, with a T1DM experience of 7±1.5 years. Total DNA was isolated from the stool samples, and sequencing libraries were prepared by amplifying the V3–V4 region of the 16S rRNA gene sequenced by Illumina MiSeq. Bioinformatic processing of NGS databases was adapted for microbiota evalutaion. Despite the broad scatter, the biological diversity for bacterial microbiota expressed as the Shannon index was significantly increased from younger to older ages in the comparison group, higher in adult healthy persons, with a trend for decrease in the Actinomycetota phylum which includes Bifidobacterium longum species. Similar but non-significant age trends were noted in the T1DM group. Concordant with the Bacillota prevalence in stool samples of diabetic patients, some anaerobic bacteria (Faecalibacteria, Lachnospira and Ruminococcae, Roseburia) were enriched in the T1DM microbiome against controls. Hence, correction of microbiota for Ruminococcus and Lachnospiraceae requires future search for new probiotics. Lower abundance of Actinomycetota and Bifidobacter in T1DM suggests potential usage of Bifidobacter-based probiotics in this cohort.